WAYS TO ACHIEVE THE MOST EFFECTIVE RESULTS BY MOTIVATING STUDENTS - Toshpulatov Ibrohim Ikromjonovich; Akbarov Soxodilla Yuldashboyevich; Karimov Jobirxon Nurillo oʻgʻli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
To increase the ability of students to freely express their thoughts and improve their knowledge, and to improve the effectiveness of education through motivational methods. Improving students’ intellectual knowledge. This article considers ways to achieve the most effective results through a psychological approach to student motivation.